Fabrication and hydrogen permeation through novel BaZr0.9Y0.1O3−δ – Cu composite ceramic-metallic membranes. (16th February 2017) - Rosensteel, Wade A.; Sullivan, Neal P.
Abstract: This study is the first report of a dense BaZr0.9 Y0.1 O3− δ – Cu (BZY–Cu) ceramic-metallic (cermet) composite membrane for high-temperature hydrogen separation. BZY serves as a proton conductor, while Cu provides electronic conductivity for charge compensation. A novel molten-copper infiltration technique is used to form a dense cermet membrane by infiltrating a porous BZY substrate. A porous BZY "skeleton" is fabricated from a spray-dried powder provided by CoorsTek, consisting of the pre-cursor oxides BaSO4, ZrO2, and Y2 O3 . The powder is dry pressed into pellets. These pellets then undergo solid-state reaction and sintering in one step at 1650 °C for 10 h to form the porous ceramic skeleton. Cu and CuO powders are mixed to form a powder containing 8 at.% O. This powder is uniaxially pressed into a pellet, that is placed on top of the BZY skeleton. The skeleton and Cu–CuO pellet are placed into a controlled-atmosphere furnace, and heated to 1200 °C in a 330 ppm oxygen environment (balance argon). Under these conditions, the liquid Cu–O spontaneously infiltrates the BZY skeleton. While dwelling at 1200 °C, the gas environment is changed to a 10 mol.% hydrogen environment (balance argon) for 12 h. Then the sample is cooled to 450 °C and annealed for 24 h to reduce residual stresses within the membrane. Electron micrographs of the resulting membranes reveal that the cermet is nearly fully dense. Hydrogen permeation through a 1.90 mm thick BZY–Cu membrane was measured as a function of temperature and hydrogen partial pressure gradient. A maximum flux of 2.42 × 10 −3 mL STP cm −2 min −1 was observed at 882 °C with a 1.0 atm hydrogen partial pressure gradient. The contribution of hydrogen evolution due to water-splitting at the sweep surface was examined by varying the humidification of the feed and sweep gas streams. Degradation of performance was not observed over the course of 30 days of testing; rather, a slight increase was seen. Electron micrographs of the BZY–Cu membrane after testing do not reveal porosity or cracking through the bulk thickness of the membrane. However morphological changes were observed at the surfaces. On the feed surface (highly reducing environment), Cu has left the BZY skeleton and formed Cu spheres on the surface. On the sweep surface, this de-wetting is more pronounced. Copper has also left the BZY skeleton and formed a nearly dense, non-hermetic layer of pure Cu. These changes effectively reduce the membrane thickness while also increasing surface roughness and the area of the gas–solid interface. This may explain the apparent increase in performance over time. Highlights: Novel BaZr0.9 Y0.1 O3− δ – Cu membranes are fabricated by molten Cu infiltration. A maximum hydrogen flux of 0.0024 mL min −1 cm −2 is observed at 882 °C. Degradation is examined by scanning electron microscopy and X-ray diffraction.